(untitled) (Globalization and Business, 2018)
The article contains general and author’s paradigms, definitions and opinions related to the topic. It is worth mentioning: In economical and managerial sphere it is necessary to formulate new concepts and paradigms that will revive management sciences and practices; To prepare higher qualified managers: it is needed to prepare the appropriate educational-training system; In globalization, in civilized countries, based on the latest economic-management concepts and paradigms the relevant business-management theory and practice is developing, which must be taken into account in our country as well; To achieve sustainable development goals it is necessary to make major changes in planning and management areas; Ecological management is the process of mobilizing resources by the organization, which is intended to solve environmental problems; The concept of synergistic economics and management should be based on the work of each person and the whole community in economical and managerial works.